KARAKTERISTIK MODAL SOSIAL DAN PERANANNYA TERHADAP PRODUKTIVITAS PERTANIAN DI KECAMATAN RAMBATAN KABUPATEN TANAH DATAR - Neng Kamarni (Universitas Negeri Padang, 2013)
This study aimed to analyze the characteristics of social capital, institutional and empowerment of the poor through the development of local institutions in an effort to alleviate poverty and at the same time in order to boost agricultural productivity in Kecamatan Rambatan Kabupaten Tanah Datar. This research was a survey conducted in District Rambatan of Tanah Datar done purposively taken as the District with a level percentage of poor households are highest in Tanah Datar district, the general livelihood is farming. Based on the survey results obtained institutional characteristics and participation shows the outcome is not good. While the variable culture and customs and trust variable results obtained good decision. These results shows of social capital in the district of institutional and community participation are not good role in society, especially the District Nagari Simawang and Nagari Koto III. But overall social capital indicators and characteristics in the Kecamatan Rambatan has shown moderate or quite good.